예방진단시스템의 데이터 신뢰성 분석 - 權東震(Dong-Jin Kweon); 陳相範(Sang-Bum Chin); 郭周植(Joo-Sik Kwak); 禹貞旭(Jung-Wook Woo); 秋鎭夫(Jin-Boo Choo) (전기학회 논문지 P권, 54(2), 2005)
Abnormal symptoms on operating conditions of power transformer are monitored by a preventive diagnostic system which prevents the sudden power failure in case of quick progress of abnormal situation. The preventive diagnostic system helps plan the proper maintenance method according to the transformer conditions via accumulated data. KEPCO has adopted the preventive diagnostic system at nine of 345kV substations since 1997. Application techniques of the diagnostic sensors were settled, but diagnostic algorithm and practical use of accumulated data are not yet established. To build up the diagnostic algorithm and effective use of the preventive diagnostic system, the reliability of the data which were accumulated in a server computer is very important. This paper describes the data analysis in the server in order to advance the reliability of the accumulated data of the preventive diagnostic system. The principles and data flows of the diagnostic sensors were analyzed, and the data discrepancy between sensors and server were calibrated.